Simulating Soil Water Content, Evapotranspiration, and Yield of Variably Irrigated Grain Sorghum Using AquaCrop. (24th May 2019) - Masasi, Blessing; Taghvaeian, Saleh; Gowda, Prasanna H.; Warren, Jason; Marek, Gary
Abstract: Use of models to simulate crop production has become important in optimizing irrigation management in arid and semiarid regions. However, applicability and performance of these models differ across regions, due to differences in environmental and management factors. The AquaCrop model was used to simulate soil water content (SWC), evapotranspiration (ET), and yield for grain sorghum under different irrigation regimes and dryland conditions at two sites in Central and Southern High Plains. Prediction error ( P e ), estimated as the difference between simulated and measured divided by measured, for SWC ranged from −17% to 4% in fully irrigated, −3% to −10% in limited irrigated, and −16% to 25% in dryland treatments. The P e within ±4%, −5%, and −17% to 24% were attained for seasonal ET under fully irrigated, limited irrigated, and dryland conditions, respectively. P e values for grain yield were within those previously reported and ranged from −10% to 12%, −12% to 7%, and 9% to 17% for fully irrigated, limited irrigated and dryland conditions, respectively. Overall performance of the AquaCrop model showed it could be used as an effective tool for evaluating the impacts of variable crop and irrigation managements on the production of grain sorghum in the study area. Finally, the application of the model in the study area revealed planting date has a significant impact on sorghum yield and irrigation requirements, but the impact of planting density was negligible. Editor's note : This paper is part of the featured series on Optimizing Ogallala Aquifer Water Use to Sustain Food Systems. See the February 2019 issue for the introduction and background to the series . Abstract : Research Impact Statement : AquaCrop is effective in simulating the response of sorghum to variable irrigation levels. It can be used to study the impact of management practices on sorghum when field experiments are unfeasible.